2368. Cellulitis in Adult Patients: A Large, Multicenter, Observational, Prospective Study of 606 Episodes, and Analysis of the Factors Related to the Response to Treatment. (26th November 2018) - Collazos, Julio; Fuente, Belen De La; Garcia, Alicia; Gomez, Helena; Menendez, Candela; Enriquez, Hector; Sanchez, Paula; Alonso, Maria; Lopez-Cruz, Ian; Martin-Regidor, Manuel; Martinez-Alonso, Ana; Guerra, Jose; et al.
Abstract: Background: Cellulitis is frequent cause of admission of adult patients to medical wards. Increasing prevalence of multiresistant microorganisms, comorbidities, predisposing factors, and medical and surgical therapies might affect cellulitis response and recurrence rate. Methods: Prospective and observational study of 606 adult patients with cellulitis admitted to the Internal Medicine wards of several Spanish hospitals. Comorbidities, microbiological, clinical, diagnostic, treatment (surgical and antibiotic) data were analyzed according to the cellulitis response. Good response implied cure. Poor response implied failure to cure or initial cure but relapse within 30 days of hospital discharge Results: Mean age was 63.3 years and 51.8% were men. Poor responses were significantly associated with age, previous episodes of cellulitis, prior wounds and skin lesions, venous insufficiency, lymphedema, immunosuppression and lower limbs involvement No differences in ESR or CRP blood levels, leukocyte counts, pus or blood cultures positivity or microbiological or imaging aspects were observed in those with good or poor responses. Regarding antimicrobials, no differences in previous exposition before hospital admission, treatment with single or more than one antibiotic, antibiotic switch, days on antimicrobials or surgical treatment were observed regarding good or poor cellulitis response. Prior episodes of cellulitis ( P = 0.0001), venous insufficiency ( P = 0.004), immunosuppression ( P = 0.03), and development of sepsis ( P = 0.05) were associated with poor treatment responses, and non-surgical trauma ( P = 0.015) with good responses, in the multivariate analysis. Conclusion: Prior episodes of cellulitis, nonsurgical trauma, venous insufficiency, sepsis and immunosuppression were independently associated with treatment response to cellulitis, but not the causing microorganism, the number of antimicrobials administered or its duration. Disclosures: All authors: No reported disclosures.